2022
DOI: 10.1109/jsen.2022.3203513
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Amperometric Sensing Mechanism in Gold–C60–Gold Molecular Dot

Abstract: We investigate through simulations the gold-C 60 -gold molecular junction as a novel single-molecule amperometric gas sensor. We find it promising for NO and NO 2 detection in air and at room temperature, with current variations of the order of the microampere, and presenting the potential capability of achieving the single-molecule sensitivity along with selectivity in the presence of common atmospheric gases. Furthermore, and for the first time, we investigate the current modulation mechanism due to target-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…A current reduction of almost two orders of magnitude, from 0.462 µA to 6.56 nA, is present in the optimum sensing condition, corresponding to AC1 configuration at 0.6 V. Interestingly, the transport modulation seems independent on the nature of the AFB1-8PyDT chemical interaction, while we believe it is caused by an 8PyDT torsion, that breaks the 8PyDT conjugation and affects the molecular channel conformation and orbitals, with spatial TEs and TPs modulation. Despite the very different sensor structure, this is coherent with the results we obtained in a previous work [36]. Thanks to the effective I DS reduction of hundreds of nA in all the AC1, AC2, AC3, AC4 cases, the proposed SMS is promising for chemically robust, labelfree, pervasive detection of AFB1 concentration in food stocks and on field.…”
Section: Discussionsupporting
confidence: 88%
“…A current reduction of almost two orders of magnitude, from 0.462 µA to 6.56 nA, is present in the optimum sensing condition, corresponding to AC1 configuration at 0.6 V. Interestingly, the transport modulation seems independent on the nature of the AFB1-8PyDT chemical interaction, while we believe it is caused by an 8PyDT torsion, that breaks the 8PyDT conjugation and affects the molecular channel conformation and orbitals, with spatial TEs and TPs modulation. Despite the very different sensor structure, this is coherent with the results we obtained in a previous work [36]. Thanks to the effective I DS reduction of hundreds of nA in all the AC1, AC2, AC3, AC4 cases, the proposed SMS is promising for chemically robust, labelfree, pervasive detection of AFB1 concentration in food stocks and on field.…”
Section: Discussionsupporting
confidence: 88%
“…In a previous work [ 25 ], we have shown that chemical analytes can significantly modify the SMS transmission spectrum, , and thus the SMS current, , through a spatial modification of the region in which transmission occurs, i.e., by modifying the contributing to conduction. In [ 25 ], we related the modification to an electron wavefunction spatial displacement caused by the presence of the analyte.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a previous work [ 25 ], we have shown that chemical analytes can significantly modify the SMS transmission spectrum, , and thus the SMS current, , through a spatial modification of the region in which transmission occurs, i.e., by modifying the contributing to conduction. In [ 25 ], we related the modification to an electron wavefunction spatial displacement caused by the presence of the analyte. In other words, the target analyte can significantly affect the electron wavefunction in the SMS by modifying the transmission properties , and , and therefore the current, , which can be evaluated through Equations ( 1 ) and ( 3 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation